Учёные Черновицкого университета : библиографический аспект исследования - Шилюк, Олег; Дячук, М. (My University, 2016)
Issues of research of scientific heritage left by the university academicians have a great meaning within the context of study of a scientific thought development on the whole and analysis of scientific development in a separate region. In this article authors have considered study of the library funds and preparation of bibliographic indices as an important element for study of heritage left by some scientists, schools of sciences and thoughts, their foundation and development. Such bibliographic indices are a source for further scientific research. Problema studierii moştenirii ştiinţifice lăsate de cadrele didactice universitare are o importanţă deosebită atât în contextul cercetării evoluţiei gândirii ştiinţifice în ansamblu, cât şi pentru analiza evoluţiei ştiinţifice a unei regiuni aparte. Autorii prezentului articol consideră examinarea colecţiilor bibliotecare şi elaborarea indicatorilor bibliografici drept element important pentru studierea moştenirii unor anumiţi oameni de ştiinţă, a unor şcoli şi idei ştiinţifice în procesul afirmării şi evoluţiei lor. Asemenea indicatori bibliografici sunt şi o sursă pentru elaborarea unor cercetării ştiinţifice ulterioare.
Keywords: Biblioteca Universităţii din Cernăuţi; Bibliographic index; Historical bibliography; Scientific heritage